Electrochemical sensing platform based on the synergistic effects of MWCNTs and ZIF-L (Zn, Co) for voltammetric determination of dopamine in the presence of uric acid - Ahlam Bazrafkan; Fariba Garkani Nejad; Reza Zaimbashi; Hadi Beitollahi (Electrochemistry Communications)
A facile, sensitive, and low-cost electrochemical sensing platform was designed by combining multi-walled carbon nanotubes (MWCNTs) with two-dimensional bimetallic zeolitic imidazolate framework with leaf-like morphology (ZIF-L (Zn, Co)) for voltammetric determination of dopamine and uric acid. The nanostructure of MWCNTs interwoven ZIF-L (Zn, Co) was prepared. The characterization methods such as FE-SEM, XRD, and EDX indicated the successful preparation of this nanostructure. Then, the application of prepared MWCNTs/ZIF-L (Zn, Co) nanocomposite in the modification of carbon paste electrode (CPE) for dopamine determination was investigated. The synergistic effects of ZIF-L (Zn, Co) and MWCNTs in MWCNTs/ZIF-L (Zn, Co)-modified CPE improved the effective surface area and electrical conductivity of the modified CPE, which enhanced the current responses at lower over-potentials towards dopamine determination compared to other CPEs, based on cyclic voltammetry (CV) studies. Under the optimal conditions, the MWCNTs/ZIF-L (Zn, Co)-based electrochemical sensor displayed a favorable response for dopamine determination with a broad linear detection range (0.001 to 900.0 μM) and limit of detection (LOD) (0.7 nM). Additionally, the MWCNTs/ZIF-L (Zn, Co)-modified CPE enabled determination of dopamine in the presence of uric acid with differentiable oxidation peak potentials. Finally, the MWCNTs/ZIF-L (Zn, Co)/CPE was applied for measuring the amounts of these species in urine sample and dopamine injection, and then the known concentrations of them were spiked into the samples, which findings showed good recoveries ranging from 97.1 % to 104.3 %.